Ethics as a rare bird: a challenge for situated studies of ethics in the engineering lab. Issue 3 (2nd September 2019) - Lee, Eun Ah; Gans, Nicholas R.; Grohman, Magdalena G.; Brown, Matthew J.
ABSTRACT: Engineering ethics cannot be reduced to the ethics of individual engineers but must be considered in situ, within the sociocultural and environmental contexts of a research or design project. We studied teams in academic engineering research laboratories and how they understood and practiced ethics in their own work. Problems arise for ethnographic methods for researching this aspect of engineering ethics; namely, voluntary ethics discussions rarely occurred in the lab. In our field site, we observed many spontaneous discussions, but engineering ethics issues were not among the topics discussed. Ethical decision-making seemed to be like a rare, shy species of bird, hard to spot, requiring methods to flush it out of hiding or attract it. We adapted structured interview and facilitated discussion protocols to accomplish this. Success was modest. The problem lies both in engineering culture and in the methodological difficulties in studying situated, distributed ethical deliberation and responsibility.